Prenatal Stress Impairs Postnatal Learning and Memory Development via Disturbance of the cGMP–PKG Pathway and Oxidative Phosphorylation in the Hippocampus of Rats - Li, Yu-jie; Yang, Li-ping; Hou, Jun-lin; Li, Xin-min; Chen, Lei; Zhu, Jiang-hui; Wang, Qi-yang; Li, Gai; Zhao, Pei-yuan; Liu, Xi-hong; Shi, Zhan-jiang (Frontiers in Molecular Neuroscience, 2020)
Clinical and animal studies had shown that prenatal stress could lead to pathological changes in embryos or fetuses. However, the mechanisms of prenatal stress affecting on offspring was not yet fully clear. In present study, the maternal rats were subjected to chronic psychological stress during pregnancy using an improved communication Box, the behavioral performance and the protein alterations in the hippocampus of offspring rats were analyzed. The results showed that prenatal stress caused postnatal growth retardation and spatial learning and memory impairment in rats. Additionally, based on iTRAQ-based proteomics analysis, 158 proteins exhibited significant differential expression (DEPs) between the two groups. Further analysis showed that these DEPs involved in different molecular function categories, and participated in several biological processes, such as energy metabolic process, learning or memory and synaptic plasticity. Moreover, the pathways enrichment showed that the Alzheimer's disease was primarily connected with cGMP-PKG (cyclic guanosine monophosphate-protein kinase G) pathway and oxidative phosphorylation. Meanwhile, the cGMP level and the expression of PKG protein were decreased significantly, and the neuronal mitochondria appeared swollen and irregular shape in hippocampus of psychological stress offspring rats. The results suggested that the maternal rats subjected to chronic psychological stress during pregnancy may impair spatial learning and memory of offspring. Its mechanism was involved in affecting the hippocampal oxidative phosphorylation process and inhibiting cGMP-PKG pathway.